MoS2-confined Rh-Zn atomic pair boosts photo-driven methane carbonylation to acetic acid - Yanan Li; Huan Liu; Jun Mao; Meng Gao; Yunlong Zhang; Qiao Zhao; Meng Liu; Yao Song; Jingting Hu; Wangwang Zhang; Rui Huang; Wu Zhou; et al. (Nature Communications)
Abstract Direct carbonylation of CH4 to CH3COOH provides a promising pathway for upgrading of natural gas to transportable liquid chemicals, in which high-efficiency CH4 activation and controllable C–C coupling are both critical but challenging. Herein, we report that highly efficient photo-driven carbonylation of CH4 with CO and O2 to CH3COOH is achieved over MoS2-confined Rh-Zn atomic-pair in conjunction with TiO2. It delivers a high CH3COOH productivity of 152.0 μmol gcat. −1 h−1 and turnover frequency of 62.0 h−1 with a superior selectivity of 96.5%, outperforming previous photocatalytic CH4 carbonylation processes. Mechanistic investigations disclose the key effect of Rh-Zn synergy in combination with photo-excited electrons from TiO2 for CH3COOH formation. The active OH species produced from O2 photoreduction on the Zn site through proton-coupled electron transfer promotes CH4 dissociation to CH3 species, which then facilely couples with adsorbed CO on the adjacent Rh site forming the key CH3CO intermediate for CH3COOH formation.